RELATIONSHIP BETWEEN THE IMPLEMENTATION OF A NUTRITION-CONSCIOUS FAMILY WITH NUTRITIONAL STATUS OF CHILDREN UNDER THE RED LINE - Sonjati, Evi; Afriani, Dini; Septiana, Hendi (PHSAJ - Public Health Sebelas April Journal, 2023)
In the current era, toddlers are malnourished due to a lack of balanced nutritional intake which has an impact on stunting participants. Short-term risks due to malnutrition are increased morbidity and mortality of developmental disorders, increased burden of care and treatment. The purpose of this study was to determine the relationship between the application of nutrition-aware families using the nutritional status of toddlers below the Red Line. The benefits of this study increase knowledge about health issues for the community, especially young mothers, the importance of perfect handling so that toddlers do not suffer from malnutrition, less, and more nutrition. The approach in this study used Cross Sectional. The independent variable in this study is the application of nutrition-aware families, the dependent variable is the nutritional status of toddlers below the red line. Data collection using field information in the form of a Guttman scale. The study was conducted at one of the health centers in Sumedang district. The population of people who have toddlers with nutritional status below the red line is 19 people. Sample using total holistic population. from the analysis it is known that there is a correlation between the application of family nutrition awareness with the nutritional status of toddlers below the Red Line using a p-value of 0.002 and an OR value of 1.853. Suggestions researchers can maintain and increase the application of nutrition-conscious family attitudes similar to adding a variety of foods and it is also expected that the community routinely brings their toddlers to the posyandu every month to determine the growth and development of their toddler nutrition.